(untitled) (Eurasian Journal of Philology Science and Education, 2023)
Improving the methodology of teaching the Kazakh language in secondary school is one of the important issues on the agenda. In modern society, the issue of improving the methods of mastering the language means of the Kazakh language by students of secondary schools in accordance with the new directions of education is also becoming relevant. After all, all cultural values in everyday life, customs and traditions of a person have always been reflected in linguistic means – the most important part of the national language-the colorful linguistic means of the Kazakh language that have developed in the national consciousness. In Kazakh linguistics and literary studies, the terms "linguistic means" and "expressive means" are used in parallel. Since it concretizes a specific concept, these terminological names are widely used in our article. An important factor contributing to the increase in the level of competition of the Kazakh language with other languages is the deepening of information about expressive means and the study of linguistic and cultural specifics arising from the integrity of the national language culture in a modern globalizing society, when the flow of information affects the personality at a high level. Therefore, in order to preserve it and transmit it from generation to generation, special methodological training programs and demonstrations of landscaping tools should be improved, especially in the secondary education system. The effectiveness of the proposed methodological system is tested experimentally. The article analyzes the features of mastering the elective subject in secondary school "Language means of the Kazakh language", the results of an associative experiment reflecting the level of fixation in the linguistic consciousness of students of visual means.